MIS-C After ARDS Associated With SARS-CoV-2. Issue 11 (November 2020) - Clouser, Katharine; Baer, Aryeh; Bhavsar, Sejal; Gadhavi, Jasmine; Li, Suzanne; Schnall, Jeremy; Weiss, Jennifer E.
Abstract : This is a case of an 11-year-old female who was admitted with respiratory failure, requiring intubation while testing positive for SARS-CoV-2. During her recovery, she had new onset fevers and uptrending inflammatory markers. After an evaluation of infectious causes, the diagnosis of MIS-C was made approximately 1 month after her initial symptoms.